1994
DOI: 10.1093/infdis/170.3.724
|View full text |Cite
|
Sign up to set email alerts
|

Changes In Vaginal Flora During Pregnancy And Association With Preterm Birth

Abstract: A prospective study of the vaginal flora changes between midtrimester and labor was undertaken in 560 women; 337 had intact membranes and were in labor when swabs were taken. Of these, 45 delivered preterm. Gardnerella vaginalis, Ureaplasma urealyticum (both associated with preterm birth when present in midtrimester), and Mycoplasma hominis commonly persisted between midtrimester and labor, particularly in the preterm cohort (24 [65%] of 37 midtrimester isolates), and these organisms were seldom acquired late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 9 publications
0
33
0
3
Order By: Relevance
“…Severe complications such as mid-trimester pregnancy losses, chorioamnionitis and even first trimester abortions were linked to the latter flora and mycoplasmata 8,17,18 . McDonald et al 9 found E. coli and group B streptococci to be important pathogens alongside the classical bacterial vaginosis organisms, and we reported that abnormal flora, but not full-blown bacterial vaginosis, was associated with preterm birth 11,19 . We hence suggested that a second abnormality of the vaginal flora should be considered, now termed 'aerobic vaginitis' 1 .…”
Section: Vaginal Fluid Constituentsmentioning
confidence: 50%
See 2 more Smart Citations
“…Severe complications such as mid-trimester pregnancy losses, chorioamnionitis and even first trimester abortions were linked to the latter flora and mycoplasmata 8,17,18 . McDonald et al 9 found E. coli and group B streptococci to be important pathogens alongside the classical bacterial vaginosis organisms, and we reported that abnormal flora, but not full-blown bacterial vaginosis, was associated with preterm birth 11,19 . We hence suggested that a second abnormality of the vaginal flora should be considered, now termed 'aerobic vaginitis' 1 .…”
Section: Vaginal Fluid Constituentsmentioning
confidence: 50%
“…No AV Mild AV Moderate / severe AV BV other 8,9 . Severe complications such as mid-trimester pregnancy losses, chorioamnionitis and even first trimester abortions were linked to the latter flora and mycoplasmata 8,17,18 .…”
Section: Vaginal Fluid Constituentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Es exclusiva de arenales costeros, donde crece formando densos tapices (McDonald, 1994;Silvestre, 2012). Los tallos son glabros y pueden alcanzar los 10 m de longitud y 2-7 mm de diámetro.…”
Section: P O M O E a I M P E R A T I ( C Ounclassified
“…Such forms of abnormal flora have been termed 'intermediate flora' in some studies, or been included with full-blown bacterial vaginosis in others. [4][5][6] This type of undefined abnormal flora may be of crucial importance in pregnant women at risk of preterm delivery. 4,6 Therefore, now it has been clear that the classifications of Candida vaginitis, Trichomonas vaginitis, and Bacterial vaginosis are insufficient to explain all clinical symptoms, therapy failures and the surprising outcomes of some studies on the link between some forms of bacterial flora and preterm birth rate.…”
Section: Introductionmentioning
confidence: 99%